Eksplorasi Pemanfaatan Media Pembelajaran dalam Pengenalan Budaya Lokal Kabupaten Jember - Widiastuti, Reski Yulina; Pradani, Dinda Shollu Putri; Khotimah, Azkia Khusnul (JCE (Journal of Childhood Education), 2025)
The fading and forgetting of local culture in Indonesia are a result of increasing technology and globalization. Teachers are expected to be able to utilize media and surrounding potential to increase children's knowledge regarding regional culture, moral values, ​​and ethics that are in accordance with cultural culture in Indonesia. This study aims to describe the use of learning media to introduce local culture. This study uses a descriptive qualitative research approach with observation, interview, and documentation data collection techniques. The data analysis technique uses Miles and Huberman analysis techniques. The study's results suggest that introducing early childhood learners to topics about local culture can be an engaging learning experience. The introduction of local culture implemented in learning includes traditional games, regional traditions, typical arts, typical foods, regional potential, and religious traditions. Teachers design local culture introduction activities in an attractive manner, utilizing a variety of learning media. Teachers utilize media available in the school environment; if the media is not available, then teachers make their own learning media by utilizing natural materials, used materials, or game materials that can be found in the surrounding environment and utilizing various learning resources that are easily accessible and simple to obtain.